2022
DOI: 10.1111/anae.15913
|View full text |Cite
|
Sign up to set email alerts
|

The safety of tranexamic acid administration in total knee arthroplasty: a population‐based study from Taiwan

Abstract: Summary Tranexamic acid is an effective treatment to reduce blood loss. We performed a retrospective observational study to evaluate safety in unilateral total knee arthroplasty. We utilised Taiwan's national health insurance database to identify relevant patients and to retrieve information on peri‐operative blood transfusions and tranexamic acid administration within 60 days of follow‐up. We examined changes in the rate of transfusions and adverse events with respect to tranexamic acid administration using l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…In this issue of Anaesthesia , Hsu et al. [5] present retrospective observational safety information on all patients receiving a total knee arthroplasty (TKA) in Taiwan. The authors used a population‐based database to retrieve data from more than 220,000 patients over a 10‐year period, of which approximately 43% received TXA.…”
Section: Safety Datamentioning
confidence: 99%
See 4 more Smart Citations
“…In this issue of Anaesthesia , Hsu et al. [5] present retrospective observational safety information on all patients receiving a total knee arthroplasty (TKA) in Taiwan. The authors used a population‐based database to retrieve data from more than 220,000 patients over a 10‐year period, of which approximately 43% received TXA.…”
Section: Safety Datamentioning
confidence: 99%
“…In the article by Hsu et al. [5], there was no fixed protocol as to dose or route of administration of TXA, and 44% of patients received between 1 g and 2 g. Studies have generally concluded that when TXA is administered to patients undergoing TKA, the optimal regimen is either 1 g intravenously before application of a tourniquet, or 1 g via the intra‐articular route during surgery.…”
Section: Safety Datamentioning
confidence: 99%
See 3 more Smart Citations